TAFSIR GENDER - Tri Wahyudi Ramdhan (LP2M Universitas Ibrahimy, 2016)
Traditional Islamic thought in general provides limited role of women as wives and mothers. Based on the view of classical Islamic texts and literature are still seen that women are still marginalized, or in other words, women are still under the domination of men. Therefore, women need to construct a discourse or text at will. It is undeniable that the interpretation of the classical scholars on the concept of equality of men and women from the perspective of today may well be judged as biased. For interpretations of the past can not be released to the socio-historical context of the time. Departing from the problems mentioned above then this article would like to see and analyze how the concepts offered and presented Islam in view of gender equality between men and women starting from the concept of gender so that the concept of gender bias by sex.Selanjutnyan followed by a discussion of the word gender mufrodat in the Qur'an and concludes with the interpretation of the discourse of gender equality. Dalama This commentary will set forth the extent where the equality between men and women